2020
DOI: 10.1007/s00281-020-00805-0
|View full text |Cite
|
Sign up to set email alerts
|

From structural modalities in perinatal medicine to the frequency of preterm birth

Abstract: Preterm birth is a global health problem that affects 11% of all live births: it remains a significant cause of death and an important cause of long-term loss of human potential among survivors all around the world. In the last decade, many developed countries have seen an increase in the rate of infants born preterm. Various theoretical and practical concepts have been discussed that aim to optimize the perinatal care of preterm infants and their mothers. These include the definition of hospitals with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Globally, 11% of newborns are preterm birth, leading to 15 million premature infants. The incidence of preterm birth is increasing in many countries, meanwhile, the survival rate of preterm babies has dramatically improved in developed countries [33,34]. Preterm birth represents a significant cause of death and can lead to serious harm to survivors all around the world [35].…”
Section: Preterm Birthpreterm Birthmentioning
confidence: 99%
“…Globally, 11% of newborns are preterm birth, leading to 15 million premature infants. The incidence of preterm birth is increasing in many countries, meanwhile, the survival rate of preterm babies has dramatically improved in developed countries [33,34]. Preterm birth represents a significant cause of death and can lead to serious harm to survivors all around the world [35].…”
Section: Preterm Birthpreterm Birthmentioning
confidence: 99%
“…lasting health impairments (49,50). Among the possible pregnancy adversities, the risk for preterm birth has likely been best investigated and the majority of studies identified a risk perpetuation caused by heat, as highlighted by a current summary on the topic (51).…”
Section: Heat Stress: a Threat To Reproductive Successmentioning
confidence: 99%
“…Deindl and Diemert highlight features of the heterogeneity of the syndrome and focus on its connection with health care structures. The authors further summarize the structural modalities required for the prevention of preterm birth by discussing various care levels of hospitals [5].…”
Section: Preterm Birth: Pathogenesis and Clinical Consequences Revisitedmentioning
confidence: 99%
“…Here, the onset of chorioamnionitis is suggested to act as a first inflammatory hit. Postnatal confrontation of the prematurely born neonate with a drastically altered antigen exposure, such as hospital-specific microbes, artificial devices, drugs, nutritional antigens, and hypoxia or hyperoxia can then create a second inflammatory hit [10].…”
Section: Preterm Birth: Pathogenesis and Clinical Consequences Revisitedmentioning
confidence: 99%